Association Between Eccentricity Index and Stroke Volume Variation in Septic Patients: A Cross-Sectional Observational Study - Julita, lda; Lubis, Bastian; Bangun, Chrismas Gideon (Jurnal Anestesi Perioperatif, 2026)
Introduction: Fluid overload (FO) is common in septic ICU patients and increases morbidity and mortality. Assessing fluid status remains challenging. Stroke Volume Variation (SVV) is a dynamic parameter of fluid responsiveness, while the Eccentricity Index (EI) reflects right ventricular geometric changes due to volume overload. This study evaluated the relationship between EI and SVV in patients with sepsis.Methods: This cross-sectional study included 29 newly diagnosed septic patients admitted to the ICU of Adam Malik Hospital. Fluid status was assessed within 24 hours after initial resuscitation (30 mL/kg crystalloids) based on the Surviving Sepsis Campaign. SVV was measured using an Ultrasonic Cardiac Output Monitor (USCOM), and EI was assessed by transthoracic echocardiography at end-systole using the Ryan protocol. FO was defined as SVV <10%.Results: Participants were 55.2% male, with a mean age of 47.17±12.25 years. Respiratory tract infection was the main source of sepsis (65.5%). A strong negative correlation was found between EI and SVV (r=–0.802; p<0.05). Significant differences in EI and SVV were observed between patients with and without FO (p<0.05).Discussion: Higher EI values were associated with lower SVV, indicating that septal deformation corresponds with fluid overload. EI may complement SVV in evaluating fluid status.Conclusion: EI shows a strong negative correlation with SVV in septic ICU patients and may serve as an adjunct parameter for fluid assessment. Further studies are required to confirm the diagnostic value.